2013
DOI: 10.1016/j.yjmcc.2012.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Regular treadmill exercise restores cardioprotective signaling pathways in obese mice independently from improvement in associated co-morbidities

Abstract: Obesity is a major health issue that impedes the ability of preconditioning and postconditioning to protect the myocardium against infarction secondary to dysregulation of kinase signalling pathways. Moreover, exercise decreases cardiovascular mortality in obese patients but the mechanism remains to be established. Wild-type (WT) and obese (ob/ob) mice were assigned to sedentary conditions or regular treadmill exercise (1h/day, 5 days/7, 4 weeks, 4° slope, 10-30 cm/s) and underwent 30 min of coronary artery oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 42 publications
6
36
0
Order By: Relevance
“…In a type 1 diabetic model, Broderick et al (7) have reported that 10 wk of continuous, moderate-intensity, treadmill running improved postischemic function in isolated perfused rat hearts subjected to ischemia-reperfusion. In a recent report by Pons and colleagues (37), decreased infarct size following treadmill running was demonstrated in a genetic model of severe obesity (ob/ob) mice that underwent in situ coronary artery occlusion followed by 24 h of reperfusion. However, it should be noted that this was an in vivo study using a model of genetic obesity lacking the gene encoding for leptin, a hormone shown to be proinflammatory and plays a role in the regulation of immunity (26,47).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a type 1 diabetic model, Broderick et al (7) have reported that 10 wk of continuous, moderate-intensity, treadmill running improved postischemic function in isolated perfused rat hearts subjected to ischemia-reperfusion. In a recent report by Pons and colleagues (37), decreased infarct size following treadmill running was demonstrated in a genetic model of severe obesity (ob/ob) mice that underwent in situ coronary artery occlusion followed by 24 h of reperfusion. However, it should be noted that this was an in vivo study using a model of genetic obesity lacking the gene encoding for leptin, a hormone shown to be proinflammatory and plays a role in the regulation of immunity (26,47).…”
Section: Discussionmentioning
confidence: 98%
“…Although exercise has been reported to induce cardioprotection and improve ischemic tolerance in nondiabetic hearts through a range of molecular mechanisms (18,38), studies in diabetic and/or obese animal models are few (7,37). In a type 1 diabetic model, Broderick et al (7) have reported that 10 wk of continuous, moderate-intensity, treadmill running improved postischemic function in isolated perfused rat hearts subjected to ischemia-reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…However, one can speculate that the comorbidity may interfere with cardioprotection by modulating mitochondrial function. An interesting study by Pons et al (2013) showed that regular treadmill exercise was able to protect the heart in obese (ob/ob) mice through the activation of prosurvival kinases (Akt, ERK1/2, GSK-3b, p70S6 kinase, AMPK) and in the absence of any improvement in metabolic profile. These findings suggest that regular exercise may have beneficial effects on the heart independently of any effect it may have on the metabolic profile.…”
Section: Diabetesmentioning
confidence: 99%
“…Similarly, Akt1 appears to be the PI3K effector that is both necessary and sufficient for physiological hypertrophy while actually inhibiting pathological hypertrophy induced by pressure overload (DeBosch et al 2006). Conversely, levels of the phosphatase and tensin homolog (PTEN), which inhibits PI3K/Akt signaling, decrease in the heart in response to exercise (Ma et al 2013;Pons et al 2013). We found that increased Akt1 expression in cardiomyocytes causes a decrease in expression of the transcription factor C/EBPb, and mice heterozygous for C/EBPb deletion recapitulate many of the cardiac phenotypes seen with exercise and are resistant to pressure-overload-induced cardiac dysfunction (Bostrom et al 2010).…”
Section: Major Pathways Implicated In the Cardiac Exercise Responsementioning
confidence: 99%